Principles and use of surveying instruments - Clendinning, J. (London Blackie And Son Ltd., 1959)
It is a fundamental rule to always work from the whole to the part. This implies precise control surveying as the first consideration followed by subsidiary detail surveying. This surveying principle involves laying down an overall system of stations whose positions are fixed to a fairly high degree of accuracy as control, and then the survey of details between the control points may be added to the frame by less elaborate methods.
Keywords: Surveying -- Principles